Prevalence of hypertension and its associated risk factors among bank workers of Kathmandu - Chataut, Jagdish; Dahal, Sumira; Shrestha, Abha; Bhandari, Mukta Singh (Journal of Kathmandu Medical College, 2020)
Background: Bank workers are exposed to risk factors which make them a potential occupational risk group for hypertension and information on the prevalence and risk factors of hypertension among bank workers in Nepal is very scarce. Objective: The aim of the study was to estimate the prevalence and associated factors of hypertension among bank employees in Kathmandu district. Methodology: A descriptive cross-sectional study was conducted among 416 bank employees of commercial banks of Kathmandu district. The information was obtained using a self-administered questionnaire in the workplace which included demographic information of individuals and other risk factors like alcohol,tobacco use and physical activity. Anthropometric measurements and blood pressure were recorded and hypertension was defined as per Joint National Committee VII criteria. Data analysis was performed using the Statistical Program for Social Sciences version 23. Results: Prevalence of hypertension was found to be 11.3%. Of the 47 participants with hypertension, 40(85.1%) were known cases while 7(14.9%) were newly diagnosed. Age, gender, marital status, overweight (BMI ≥25), smoking, alcohol consumption, having diabetes, and family history of -hypertension were found to have significant association with hypertension in univariate analysis. The multivariate logistic regression analysis revealed that gender, having diabetes and physical activity had independent and significant association with hypertension.Conclusion: Based on the findings from the study, we can conclude that hypertension is significantly associated with gender, physical activity and diabetes. Measures for early detection of hypertension and diabetes are required and health education regarding lifestyle modifications is recommended.